PENGARUH PERMAINAN EDUKASI GEOMETRY MAGIC TERHADAP KEMAMPUAN PENGENALAN BENTUK GEOMETRI PADA ANAK USIA 4-5 TAHUN Di TK AISYIYAH BUSTANUL ATHFAL KECAMATAN SENTAJO RAYA KABUPATEN KUANTAN SINGINGI - Riti Parwati; Devi Risma; Rita Kurnia (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: Based on the results of field observation abilities against the introduction of geometric protege undeveloped with optimum. So the need for use of educational games geometry magic. The purpose of the study is to investigate the influence of educational games Geometry recognition capabilities against Magic geometric shapes children aged 4-5 years. This research was conducted in kindergarten Bystanul Aisyiyah Athfal Marsawa Sub Regency Kuantan Singingi Sentajo Kingdom from January until April 2019 2019 for observation and research. This research is experimental research design using one group pretest and posttest design with a total sample of 16 children. Data collection techniques used in this research is the observation sheet recognition capabilities using geometric shapes. Data analysis techniques using a t-test test by using SPSS program ver 20. From the results of the analysis of the data obtained thitung of larger 20.300 dati ttabel = 2.131 with sig 0000 < 0.05. . It can be concluded that there is a difference in the ability of the introduction of a significant form of geometry before and after the educational game using Geometry Magic. Based on the hypothesis test is obtained there is the influence of educational games Geometry recognition capabilities against Magic geometric shapes on children aged 4-5 years in kindergarten Aisyiyah Bustanul Athfal Sub Regency Kuantan Singingi Sentajo Kingdom.Key Words: Geometry Of Magic, The Ability Of The Introduction Of Geometric Shapes